ASSESSMENT IN THE IMPACT OF FACEBOOK TO THE GRADE 6 STUDENT’S BEHAVIOR (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2026)
Facebook remains the preferred social media platform for approximately half of all users, underscoring its role as a key space for information sharing, self-expression, and online interaction (Statista, 2020). This study examines the impact of Facebook activities—such as posting self-content, commenting, and sharing posts—on students' self-esteem, mental health, and negative emotions. It investigates how these online behaviors influence their attitudes and behaviors as students, shedding light on the psychological effects of social media engagement.       . This study employed a quantitative research approach, which involves collecting and analyzing numerical data to identify trends, averages, and make projections to larger populations. To ensure a representative sample, the researchers used simple random sampling based on the target respondents' criteria. On a designated day, a total of two hundred (200) Grade 6 students from Tandang Sora Elementary School were randomly selected as participants, with all 200 students included in the study sample. This method allowed for a comprehensive analysis of the data within the defined group. To analyze and present the data, the researcher applied statistical methods such as frequency and percentage, composite weighted mean, and the Likert scale. The findings revealed that demographic factors such as age, gender, gadget usage, and time spent on Facebook significantly influence students' use of the platform. The study examined variables like self-posting, commenting, sharing posts, self-esteem, mental health issues, and negative emotions. The data was interpreted as indicating agreement across all variables, suggesting a clear connection between Facebook activities and students' emotional and mental well-being. To develop emerging guidelines for the positive use of Facebook, the researcher draws conclusions from the study’s findings. It is acknowledged that these guidelines can help students engage with Facebook in a more constructive and beneficial way. A set of guidelines was created based on the key variables identified in the second problem statement. The study also explores the connection between Facebook's influence and Faiswal Kasirye's Gratification Theory (2022). This theory plays a key role in understanding the relationship between media and individuals' needs and actions. It underscores the active role users play in engaging with media to meet their personal goals. The research highlights the complexity of social media's impact on daily life, mental health, and productivity, demonstrating its profound effect on users' well-being and behaviors.
Keywords: emerging guidelines; positive use of facebook; gratification theory; facebook influence; mental health; productivity; social media impact; student engagement; media users; constructive use